construction ‘εἶναι + participle’ in Homeric Greek: prototype analysis and the morphosyntax-semantics interface (ACME, 2024)
This contribution addresses the periphrasis ‘εἶναι + participle’ in Homeric Greek at the interface between morphosyntax and semantics. The data are examined with reference to the theoretical framework elaborated by Nardi and Romagno (2022), who regard the Ancient Greek εἶναι-periphrasis as a prototype category: according to this view, the superordinate category ‘εἶναι + participle’ includes two formally different, but functionally equivalent manifestations, a pattern with an expressed copula, i.e. a periphrasis tout-court, and a pattern with no overt copula, i.e. a predicative participle (basically, a participle functioning as a finite form). This investigation aims to assess if factors underlying or determining the usage of these participial constructions in Homeric Greek can be singled out. The analysis of the data individuated in the Homeric poems shows that the participial constructions encode the specific function of signifying the state, either inherent or attained, of the subject of the predicate, thus constituting a (more or less free) alternative to the original perfect (cfr. Romagno 2005).
Keywords: Homeric Greek; periphrasis; predicative participle; prototype theory; morphosyntax-semantics interface